Differential diagnosis of cervical lymphadenitis mimicking malignancy due to tularemia: Our experiences - Vedat Turhan; Ufuk Berber; Abdullah Haholu; Murat Salihoglu; Asim Ulçay (Wolters Kluwer Medknow Publications, 2013)
Background: Tularemia is a disease caused by a Gram-negative coccobacillus Francisella tularensis. This bacterium may cause different types of clinical pictures owing to acquisition route and entrance site, such as ulceroglandular, oropharyngeal, glandular, pneumonic, typhoid and ocular forms. Oropharyngeal tularemia (OPT) is the most common form of tularemia in some regions. OPT may cause tonsillopharyngitis followed by cervical lymphadenopathies (LAPs). Without treatment LAP may persist for several months and may mimic other diseases causing cervical LAPs. Materials and Methods: A total of six cases of OPT, five male and one female, between 21 and 31 years old, diagnosed serologically and clinically recorded in GATA Haydarpasa Training Hospital were included in this study. Detailed story including the region they lived for last 6 months, their occupation, family and neighborhood story with similar complaints were obtained. Patient data were also obtained from manually written patients files and electronical patient file system. Formalin fixed paraffin embedded tissue blocks of all biopsy material were submitted for polymerase chain reaction (PCR) study for F. tularensis. Results: A total of six cases with head and neck mass following a story of tonsillopharyngitis admitted to different clinics including infectious diseases, ear-nose-throat and internal medicine in our tertiary care hospital. Physical examination revealed immobile, hard, conglomerated unilateral cervical lymphadenopathy in all cases. Histopathological examination revealed granulomatous inflammation in four cases. Acute suppurative inflammatory changes were also seen in two cases. Large necrotic areas mimicking casseifying necrosis were seen in two cases. PCR amplification of F. tularensis genom from isolated deoxyribonucleic acids was successful in five cases. Conclusion: Tularemia should be kept in mind in patients with tonsillopharyngitis not responding to penicillins and beta lactam antibiotics. Furthermore, persisting LAPs mimicking tumor with or without the story of previously experienced sore throat or tonsillopharyngitis in past few days or weeks should be evaluated for glandular or OPT. At this point, easily applicable serological tests such as tularemia micro-agglutination tests will confirm the diagnosis of OPT. However, if lymph node were already sampled to exclude especially malignancy or T cell lymphoma, tularemia PCR test may be used to make a certain diagnosis.